2002
DOI: 10.1097/00005768-200205000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reduced ambient temperature on fat utilization during submaximal exercise

Abstract: The diminished fat oxidation at colder temperatures potentially reflects a reduction in lipolysis and/or mobilization of FFA or impairment in the oxidative capacity of the muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 26 publications
2
37
1
2
Order By: Relevance
“…In another study, researchers found that trigeminal nerve stimulation using cold sprays and fan on the face was associated with a reduction in heart rate during exercise [14]. Although these mechanisms should be further investigated by measuring skin blood flow and stroke volume, our current results suggest that even mild body cooling reduces heart rate during exercise, similar to previously published data [3][4][5][6].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In another study, researchers found that trigeminal nerve stimulation using cold sprays and fan on the face was associated with a reduction in heart rate during exercise [14]. Although these mechanisms should be further investigated by measuring skin blood flow and stroke volume, our current results suggest that even mild body cooling reduces heart rate during exercise, similar to previously published data [3][4][5][6].…”
Section: Discussionsupporting
confidence: 89%
“…Exposure to severe cold with a decrease in rectal and skin temperatures has been shown to enhance fat oxidation during running and walking [3] while lipid and carbohydrate oxidation during submaximal exercise does not differ between mild cooling and neutral environments [5]. In our study, skin temperature was decreased by mild body cooling, while the rectal temperature did not differ between the two trials.…”
Section: Discussioncontrasting
confidence: 41%
See 3 more Smart Citations